The anti-inflammatory effect of ferulic acid is via the modulation of NFκB-TNF-α-IL-6 and STAT1-PIAS1 signaling pathways in 2-methoxyethanol-induced testicular inflammation in rats - Olubisi E. Adeyi; Oluwatobi T. Somade; Babajide O. Ajayi; Adewale S. James; Taiwo R. Adeboye; Daniel A. Olufemi; Ebunoluwa V. Oyinlola; Ebenezer T. Sanyaolu; Iyabode O. Mufutau (Elsevier, 2023)
Background: Ferulic acid (FAC) is a component of plant cell walls, where it serves as a building block of lignin and pectin. As such, it is abundantly found in vegetables and other plants. In contrast, 2-methoxyethanol (2METH) is a testicular toxin commonly found in products used by humans. This study is aimed to investigate the effect of FAC on 2METH-induced testicular inflammation in rats. Method: Four groups of 5 animals each were used: Group I served as the control, Group II was exposed to 2METH only (100 mg/kg), Group III was administered 2METH (100 mg/kg) plus FAC (50 mg/kg), and Group IV served as the FAC (50 mg/kg) only group. All administrations were done orally for 30 days. Results: At the end of the study, rats administered 2METH only showed a significant increase in the testicular levels of interleukin 6 (IL-6), tumor necrosis factor-alpha (TNF-α), inducible nitric oxide synthase (iNOS), cyclooxygenase 2 (COX-2), and nuclear factor κB (NF-κB), as well as RNA gene expressions of Janus kinase 1 (JAK1), signal transducer and activator of transcription 1 (STAT1), and suppressor of cytokine signaling 1 (SOCS1) compared to the control group. In contrast, treatment with FAC led to a significant decrease in the testicular levels of IL-6, TNF-α, iNOS, COX-2, NF-κB, and gene expression of STAT1, while significantly increasing the testicular gene expression of protein inhibitor of activated STAT 1 (PIAS1) compared to rats exposed to 2METH only. Conclusion: Based on the data gathered from this study, FAC demonstrated an anti-inflammatory effect by inhibiting the testicular activation of NF-κB through the downregulation of pro-inflammatory markers (IL-6, TNF-α, iNOS, and COX-2) and the inhibition of the STAT1-PIAS1 signaling pathway in rats.